Memoria de trabajo y habilidades matemáticas en estudiantes de educación básica - Hernández Suárez, Cesar; Méndez Umaña, Juliana Paola; Jaimes Contreras, Luis Alberto (Revista Científica, 2021)
Recent research has shown that working memory is essential for the development of mathematical skills. The aim of the study was to study the mediation of mathematical ability with respect to working memory in a group of students. The design is non-experimental, quantitative, and correlational; for the evaluation of variables the Neuropsychological Assessment of Children Battery and a test on mathematical skills in a group of primary school students were used. The data analysed indicate that a significant correlation is found between working memory and mathematical skills in the assessed group. A training of the working memory range can significantly strengthen the students' mathematical skills.